Globalization of Law and Evolution of Constitutional Values - M.T.Turgunov (Peerian Journals Publishing, 2022)
In this article, the author considers the development and consolidation of constitutional values, which are the result of the progressive development of society as common values for all citizens of the state, clothed in a constitutional legal form, and represent fundamental, generalized, strategic priorities (goals, principles) of development society and the state. In addition, the problems of foreign constitutional comparative studies are analyzed in the context of the development of "constitutional values".
Keywords: Constitution; comparative studies; development; evolution